Profil Keakuratan Komunikasi Matematis Mahasiswa Calon Guru Ditinjau dari Perbedaan Jender - Iswita Dewi (Didaktik Matematika, 2014)
Mathematical communication is the process of delivering ideas/thoughts mathematics both written and orally. Due to convey the idea of pure mathematics can not be delivered orally without writing, the oral mathematical communication in this research is the class presentation of mathematical communication is conveyed through speech or writing related to the speech. The purpose of this study was to determine the accuracy of mathematical communication profile student teachers in solving mathematical problems in terms of gender differences and differences in mathematical ability. Based on the analysis of data it can be concluded in oral mathematical communication, male students convey information more accurately than female students.